Sociological Analysis of the Media’s Role in Advancing Diversity, Social Inclusion and Comprehensive Sexual Education in Morocco - Adaoui, Zouhir; Boukhriss, Faouzi; Ghazouani, Driss El (Journal of Education Review Provision, 2025)
This article aims to present the findings of both quantitative and qualitative research conducted among a sample of Moroccan children, adolescents, and young people. The primary goal of this research is to promote the improvement of accessibility for children, adolescents, and young people to sexual and reproductive health rights and services in a context of diversity through television. To conduct this research, we chose a sample of 200 units providing quantitative data, and others providing qualitative data, including 10 semi-structured interviews. The selection of this sample is based on a range of different sociodemographic characteristics (gender, age, education level, marital status, activity etc.). Moreover, there is an urgent need for sexual and reproductive health rights among young people and teenagers due to their growing awareness of its importance in addressing a range of negative aspects within society. This is linked to the fact that most of the interviewees have a education level. In contrast, there is a significant absence of these rights in media content on Moroccan television.